IFITM proteins drive type 2 T helper cell differentiation and exacerbate allergic airway inflammation. Issue 1 (9th November 2018) - Yánez, Diana C.; Sahni, Hemant; Ross, Susan; Solanki, Anisha; Lau, Ching‐In; Papaioannou, Eleftheria; Barbarulo, Alessandro; Powell, Rebecca; Lange, Ulrike C.; Adams, David J.; Barenco, Martino; Ono, Masahiro; et al.
Abstract: The interferon‐inducible transmembrane ( Ifitm / Fragilis ) genes encode homologous proteins that are induced by IFNs. Here, we show that IFITM proteins regulate murine CD4 + Th cell differentiation. Ifitm2 and Ifitm3 are expressed in wild‐type (WT) CD4 + T cells. On activation, Ifitm3 was downregulated and Ifitm2 was upregulated. Resting Ifitm ‐family‐deficient CD4 + T cells had higher expression of Th1‐associated genes than WT and purified naive Ifitm ‐family‐deficient CD4 + T cells differentiated more efficiently to Th1, whereas Th2 differentiation was inhibited. Ifitm ‐family‐deficient mice, but not Ifitm3 ‐deficient mice, were less susceptible than WT to induction of allergic airways disease, with a weaker Th2 response and less severe disease and lower Il4 but higher Ifng expression and IL‐27 secretion. Thus, the Ifitm family is important in adaptive immunity, influencing Th1/Th2 polarization, and Th2 immunopathology. Abstract : The interferon‐inducible transmembrane (IFITM) proteins influence Th1/Th2 polarization and promote Th2 differentiation. In absence of IFITM proteins, CD4 T‐cell differentiation is biased towards Th1, by a cell‐autonomous mechanism. IFITM‐deficient mice are less susceptible to induction of allergic airways disease by inhibition of the Th2 response and inflammation.